Relationship between erosive tooth wear and possible etiological factors among dental students - KARGÜL, BETÜL (My University, 2022)
Objectives The aim of this study was to assess the relationship between erosive tooth wear (ETW) and possible etiological factors in a group of dental students. Materials and methods A total of 126 dental students from a public dental school were included in this study. A questionnaire was used to investigate the possible etiological factors related to ETW. The Basic Erosive Wear Examination (BEWE) criteria were used to examine the status of ETW. A univariable and multivariable logistic regression models were used to assess the relationship between the presence of ETW and explanatory variables. Results Univariable analysis revealed that taking acidic foods and alcohol more than 4-5 times per week increases the odds of ETW by 6.043 and 2.532 times, respectively, and taking dairy products, fruit juice, and milk more than 4-5 times per week decreases the likelihood of ETW by 61%, 66%, and 80%, respectively. The results of multivariable regression analysis showed that the frequency of consumption of especially acidic foods significantly increased the risk of ETW (OR = 9.981, 95% CI 3.577-27.849, p < 0.001). Conclusions Although the ETW status of dental students, who are the future dentists, varies depending on different possible etiological factors, especially the consumption of acidic foods has increased the risk of ETW approximately 10 times. Clinical relevance The fndings highlight the high relevance of ETW, especially with acidic food consumption, and the importance of controlling potential etiological factors in dental students.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Orthodontics; Oral Surgery; Dentistry (miscellaneous); Dental Hygiene; Periodontics; Dental Assisting; General Dentistry; Dental erosion; Dental students; Erosive tooth wear; Prevention and control; Questionnaire; RISK-FACTORS; PREVALENCE; DIAGNOSIS; KNOWLEDGE; ENAMEL; Dental erosion; Dental students; Erosive tooth wear; Prevention and control; Questionnaire